Percutaneous Mitral Valvuloplasty Using Echocardiographic Intercommissural Diameter as Reference for Balloon Sizing: A Randomized Controlled Trial - Sanati, Hamid Reza (Clin Cardiol, 2012)
BACKGROUND: Percutaneous balloon mitral valvuloplasty is the preferred therapeutic strategy in patients with mitral stenosis, but it has shortcomings in a subset of patients. HYPOTHESIS: A new method of balloon sizing through echocardiographic measurement of the intercommissural diameter would be safe and effective and lead to better outcomes. METHODS: Eighty‐six mitral‐stenosis patients were randomly assigned to undergo balloon mitral valvuloplasty either with height‐based balloon reference sizing (HBRS group, n = 43) or with balloons sized by the echocardiographic measurement of intercommissural diameter (EBRS group, n = 43). Postprocedural mitral valve area (MVA) and severity of mitral regurgitation (MR) were assessed via echocardiography and ventriculography. Intention‐to‐treat approach was applied for the statistical analysis. RESULTS: Baseline characteristics were not different between the groups. The mean of the estimated balloon reference sizes was significantly higher in the HBRS patients than in the EBRS group (26.4 ± 0.92 mm, 95% confidence interval [CI]: 26.2–26.6 vs 24.5 ± 1.03 mm, 95% CI: 24.2–24.7, respectively; P = 0.006). Final MVAs were significantly larger in the EBRS group (1.5 ± 0.2 cm(2), 95% CI: 1.46–1.59 vs 1.4 ± 0.2 cm(2), 95% CI: 1.35–1.47, respectively; P = 0.01). The occurrence of new or aggravated MR was significantly lower in the EBRS group as assessed both by echocardiography (P = 0.04) and ventriculography (P = 0.05). Mitral regurgitation was aggravated in 13 (29.3%) patients in the HBRS group and in 5 (11.5%) patients in the EBRS group. CONCLUSIONS: Percutaneous balloon mitral valvuloplasty via the Inoue technique using balloons sized by the echocardiographic measurement of the maximal commissural diameter is an effective and safe method that might lead to an acceptable increase in the MVA and significant decrease in the rate and severity of iatrogenic MR. The results of this work were orally presented in part at EuroPCR, Paris, France, May 17‐20, 2011. The authors have no funding, financial relationships, or conflicts of interest to disclose.